Structure, Value and Context of Tembang Pisaan Culture in Runjung Agung District - Yuliya, Yezi; Missriani; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to identify and describe the structure, values, and cultural context of the Tembang Pisaan oral literature. The research method used is descriptive qualitative research method because literature is a form of creative work that is constantly changing. Data collection techniques used; observation, interviews, documentation and recording techniques. The data analysis technique used is; domain analysis, taxonomic analysis, component analysis, and culture theme analysis. The result of this research is that the oral literature of Tembang Pisaan has a physical and mental structure. Meanwhile, the value analysis in this study is cultural values ??and religious values, namely those concerning the relationship between man and God, human relationship with society, and human relationship with himself. The cultural context is in the form of its application in society, because the pisaan song is rich in customs, moral messages, advice, and cultural treasures that are useful for the supporting community.